From Data to Manuscript: A Strategy for Young Oncologists to Write a Scientific Paper - Auro del Giglio; Daniel Iracema Gomes de Cubero; Mateus Uerlei Pereira da Costa (Brazilian Journal of Oncology)
Scientific manuscripts are the basis for the transmission of scientific data among physicians in all fields of medicine. To teach young oncologists the skills needed to author a paper, we decided to emulate how experienced clinicians perform this task. The first step is to create a spreadsheet with all the clinical data gathered and submit it to a statistical analysis using a statistical software package. The most important results are presented in the graphs and tables. The results should be explained in a logical and understandable manner. Writing the “Materials and Methods” section follows, with all the technical information that any other researcher may need to reproduce elsewhere the study in question. A critical-thinking stage, in which a review of the pertinent literature is conducted with the use of a reference management software, should provide all the knowledge and questions to write the “Introduction” and “Discussion” sections. The “Abstract” and “Title” are the final sections to be created. Following these steps, the author can correct the first draft of the manuscript for submission to a specific journal. Choosing the right journal and answering the reviewers' comments are also important steps in this process. Even if a young oncologist does not embark on an academic career, learning how to write a scientific manuscript is believed to be the best way to teach them how to read such manuscripts during their lifelong continuous self-education.